The Influence of Education Management, Transformational Leadership, and Teacher Performance Effectiveness on Student Learning Outcomes at SMAN 1 Dolok Pardamean Simalungun Regency - Mario Asido Sipayung; Innocentius Bernarto (CV. Publikasi Indonesia, 2025)
This research examines the influence of education management, transformational leadership, and effective teacher performance on student learning achievement at SMAN 1 Dolok Pardamean, Simalungun Regency. Based on observations and interviews, it was found that effective education management, transformational leadership, and optimal teacher performance contribute to improving student learning outcomes. This research used a quantitative approach with the SEM-PLS method to analyze the relationship between variables. The research subjects were 41 SMAN 1 Dolok Pardamean teachers in the odd semester of the 2024/2025 school year. The results of the analysis show that education management, transformational leadership, and teacher performance positively affect student learning achievement. The path coefficients for each variable are 0.312, 0.342, and 0.373, with a p-value <0.05, indicating a significant effect. The model can explain 76.7% of the variance in student learning outcomes. The findings confirm the importance of effective education management implementation and transformational leadership in improving learning quality and student learning outcomes.